Curcumin protects retinal neuronal cells against oxidative stress-induced damage by regulating mitochondrial dynamics. (November 2022) - Xu, Dan; Zhang, Kun; Qu, Xin-Hui; Wang, Tao; Yang, Ping; Yang, Yun; Jiang, Li-Ping; Wan, Yu-Ying; Tou, Fang-Fang; Chen, Zhi-Ping; Han, Xiao-Jian
Abstract: Oxidative stress plays a crucial role in the damage of retinal neuronal cells. Curcumin, the phytocompound, has anti-inflammatory and antioxidative properties. It was shown that curcumin exerted a beneficial effect on retinal neuronal cell survival. However, the role of mitochondrial dynamics in curcumin-mediated protective effect on retinal neuronal cells remains to be elucidated. Here, H2 O2 was used to mimic the oxidative stress in retinal neuronal R28 cells. Drp1 and Mfn2 are key regulators of mitochondrial fission and fusion. 100 μM of H2 O2 significantly increased the cleavage of caspase-3 and Drp1 expression, but downregulated the expression of Mfn2. Pretreatment with 5 μM curcumin effectively alleviated H2 O2 -induced alterations in the expression of Drp1 and Mfn2 and mitochondrial fission in R28 cells. In addition, curcumin and Drp1 knockdown prevented H2 O2 -induced intracellular ROS increment and mitochondrial membrane potential disruption. On the contrary, knockdown of Mfn2 diminished curcumin-mediated protection against ROS increment and mitochondrial membrane potential disruption after H2 O2 . Moreover, curcumin protected R28 cells against H2 O2 -induced PINK1 expression, mitophagy, caspase-3 cleavage and apoptosis. Knockdown of Mfn2 significantly alleviated the protective effect of curcumin on R28 cells after H2 O2 . Taken together, our data indicate that curcumin protects against oxidative stress-induced injury in retinal neuronal cells by promoting mitochondrial fusion. Highlights: 1, H2 O2 induced mitochondrial fission, mitophagy and apoptosis in retinal neuronal R28 cells. 2, Mitochondrial dynamics plays the key role in oxidative stress-induced damage in retinal neuronal cells. 3, Curcumin protected retinal neuronal cells against oxidative stress-induced damage by promoting mitochondrial fusion.